From Zero-shot to Self-generated References: Leveraging LLMs for Scoring ENEM Essays - Utino, Matheus Yasuo Ribeiro; Mann, Paulo (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2025)
This study investigates the application of Large Language Models (LLMs) to Automated Essay Scoring (AES) in the context of Brazil’s Exame Nacional do Ensino Médio (ENEM). We evaluate five state-of-the-art LLMs across three prompting scenarios: zero-shot, one-shot (with high-score references), and a novel self-generated reference approach, where the model generates its own ideal reference before evaluation. Using the Essay-BR corpus, we assess performance using both classification and regression metrics. Results show that one-shot prompting consistently yields the best metrics, while the self-generated reference method presents a viable alternative when no real references are available. Our findings highlight the promise of LLMs for educational scoring.